DIETARY CARBOHYDRATE AND PHYSICAL ACTIVITY WITH PREDIABETES WITHIN ADULT WOMEN - Khoiriyah, Dian; Murbawani, Etisa Adi; Panunggal, Binar (Tadulako University, 2017)
Background & Objective: Prediabetes is a high-risk condition for developing diebetes mellitus. Adult women have a higher risk of experiencing prediebetes compared with men. Excessive of simple carbohydrate intake, low of fiber intake and physical activity risk to increasing blood glucose levels. This study aimed to analyze the correlation between total carbohydrate intake, simple carbohydrate intake, fiber intake and physical activity with prediabetes in adult women. Materials and Methods: This study used a case control with 36 women aged 45-55 years old in each group chosen by simple random sampling. Food intake was assessed using by Semi FFQ. Waist circumference was measured using by a tape measure, and physical activity was obtained using by Long IPAQ. Data were analyzed using by Chi Square, Fisher Exact and multiple logistic regression test. Results: There is a difference in mean of waist circumference, fasting blood glucose, simple carbohydrate intake, fiber intake and physical activity in both groups. The variable at risk for prediabetes were simple carbohydrate intake (OR=3,94;95%CI 1,23-12,56), fiber intake (OR=2,63;95%CI 0,91-7,63) and fat intake (OR=2,14;95%CI 0,78-5,84). Intake of simple carbohydrate and fiber are the most dominant variable that affecting the incidence of prediabetes with a proportion of 14,5%. There were no correlation between total carbohydrate intake, fiber intake and physical activity with prediabetes in adult women. Conclusion: Excessive simple carbohydrate intake and low fiber intake were risk in the occurrence of prediabetes